A water crisis without Langat 2 - Ahmad Sabri, Ahmad Zaharuddin Sani (New Straits Times, 2012)
alternative needed: Universiti Utara Malaysia's College of Arts and Sciences senior lecturer Dr Ahmad Zaharuddin Sani says there is a need to take action to resolve the water crisis in Selangor and put in place a longterm, viable solution to ensure future water needs